Formation of NDMA by chloramination of nitrogenous contaminants: Potential role of bromide and dissolved oxygen - Le Roux, J.; Gallard, H.; Croue, Jean-Philippe (2011)
Disinfection with monochloramine is known to significantly reduce the formation of regulated disinfection by-products (i.e. trihalomethanes and haloacetic acids) as compared to chlorination. Moreover, monochloramine can be added to wastewater prior to reuse processes to avoid biofouling of membranes. However, chloramination favors the formation of N-nitrosamines, including N-nitrosodimethylamine (NDMA), a probable human carcinogen. Proposed NDMA formation mechanisms used dimethylamine as a model precursor, but some anthropogenic tertiary amines presenting dimethylamine functional groups have been demonstrated to lead to important amounts of NDMA (e.g. ranitidine, a histamine antagonist used for peptic ulcer treatment). In this study, NDMA formation potential of several tertiary amines from the reaction with monochloramine is investigated. Compounds presenting heterocyclic rings substituted with DMA functions (e.g. ranitidine) show much higher conversion rates to NDMA than other tertiary amines or DMA. The concentration of dissolved oxygen was found to play a major role: with ranitidine, in the absence of dissolved oxygen almost no NDMA was formed, while the NDMA molar yield was 54% in saturated O 2 solution. The presence of bromide also significantly enhanced the formation of NDMA during chloramination of dimethylamine and dimethylaminomethyl-furfuryl alcohol. This may be related to the formation of reactive brominated oxidants such as bromochloramine (NHBrCl). These results are of great concern regarding wastewater reuse, because the chloramination of bromide-containing wastewaters could lead to significant amounts of NDMA. 2011 © American Water Works Association AWWA WQTC Conference Proceedings All Rights Reserved.